Insights into Frizzled evolution and new perspectives. Issue 2 (March 2015) - Schenkelaars, Quentin; Fierro‐Constain, Laura; Renard, Emmanuelle; Hill, April L.; Borchiellini, Carole
SUMMARY: The Frizzled proteins (FZDs) are a family of trans‐membrane receptors that play pivotal roles in Wnt pathways and thus in animal development. Based on evaluation of the Amphimedon queenslandica genome, it has been proposed that two Fzd genes may have been present before the split between demosponges and other animals. The major purpose of this study is to go deeper into the evolution of this family of proteins by evaluating an extended set of available data from bilaterians, cnidarians, and different basally branching animal lineages (Ctenophora, Placozoa, Porifera). The present study provides evidence that the last common ancestor of metazoans did possess two Fzd genes, and that the last common ancestor of cnidarians and bilaterians may have possessed four Fzd . Furthermore, amino acid analyses revealed an accurate diagnostic motif for these four FZD subfamilies facilitating the assignation of Frizzled paralogs to each subfamily. By highlighting conserved amino acids for each FZD subfamily, our study could also provide a framework for further research on the precise mechanisms that have driven FZD neo‐functionalization.